Management of psoriasis in adolescence - Fotiadou C; Lazaridou E; Ioannides D (Dove Medical Press, 2014)
Christina Fotiadou, Elizabeth Lazaridou, Demetrios Ioannides First Department of Dermatology–Venereology, Aristotle University Medical School, Thessaloniki, Greece Abstract: Psoriasis is a chronic inflammatory cutaneous disorder affecting 2%–4% of the world's population. The prevalence of the disease in childhood and adolescence ranges between 0.5% and 2%. The management of psoriasis in adolescence is an intriguing and complicated task. Given the paucity of officially approved therapies, the very limited evidence-based data from randomized controlled trials, and the absence of standardized guidelines, physicians must rely on published experience from case reports both from the field of dermatology as well as from the application of these drugs for other pediatric conditions coming from the disciplines of rheumatology, gastroenterology, and oncology. Psoriatic adolescents deal with a potentially disfiguring and lifelong disease that could permanently impair their psychological development. It must be clarified to them that psoriasis does not have a permanent cure, and therefore the main goal of treatments is to establish disease control and prolonged periods between flares. The majority of adolescents suffer from mild psoriasis, and thus they are treated basically with topical treatment modalities. Phototherapy is reserved for adolescents with mild-to-moderate plaque disease and/or guttate psoriasis when routine visits to specialized centers do not create practical problems. Systemic agents and biologics are administered to patients with moderate-to-severe plaque psoriasis, pustular psoriasis, or erythrodermic psoriasis. Keywords: adolescent psoriasis, pediatric psoriasis, treatment, systemic treatment, biologic agents